Synthesis and Structural Features of Hydrogen-Bonded Networks Based on The Combination of _x000D_ Tectons Triphenylboroxine Cation and Pt$(SCN)_4$ Anion Salts - (:unkn) unknown (My University, 2021)
In this work, a new compound [$C_15H_16B_3N_3O_5$].[Pt$(SCN)_4$].2($H_2O$] (1) has been _x000D_ synthesized and structurally characterized. The compound (1) crystallizes in monoclinic, space group _x000D_ $P2_1$/c a=10.443 Å, b= 24.918 Å, c= 15.048 Å, ??=90_x000D_ , β=133.945_x000D_ , γ=90_x000D_ , V=2819.4 $Å^3$_x000D_ , Z=4. The use _x000D_ of molecular tecton (building block) able to form thiocyano-based hydrogen-bonded synthons _x000D_ (OH···SCN) to synthesize a diverse range of crystal structures is described. In the crystal structure, _x000D_ molecules are linked by intermolecular SCN···HN and BO···HN hydrogen bonds, forming a three?dimensional network._x000D_